2007
DOI: 10.1257/aer.97.2.316
|View full text |Cite
|
Sign up to set email alerts
|

Aid Effectiveness—Opening the Black Box

Abstract: The empirical literature on aid effectiveness has yielded unclear and ambiguous results. This is not surprising given the heterogeneity of aid motives, the limitations of the tools of analysis, and the complex causality chain linking external aid to final outcomes. The causality chain has been largely ignored and as a consequence the relationship between aid and development has been mostly handled as a kind of 'black box'. Making further progress on aid effectiveness requires opening that box. This paper exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
138
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(144 citation statements)
references
References 3 publications
0
138
1
2
Order By: Relevance
“…As previously noted, some econometric studies have suggested that foreign aid flows may be large enough to have a significant effect on political accountability in recipient countries (Brautigam and Knack 2004;Djankov, Montalvo, and Reynal-Querol 2005), but the econometric devices these studies employ are not widely accepted by critics (Bourguignon and Sundberg 2007).…”
Section: Foreign Assistance and Revenue Bargainingmentioning
confidence: 99%
“…As previously noted, some econometric studies have suggested that foreign aid flows may be large enough to have a significant effect on political accountability in recipient countries (Brautigam and Knack 2004;Djankov, Montalvo, and Reynal-Querol 2005), but the econometric devices these studies employ are not widely accepted by critics (Bourguignon and Sundberg 2007).…”
Section: Foreign Assistance and Revenue Bargainingmentioning
confidence: 99%
“…Further studies lead to an emerging consensus that, at best, there appears to be a small positive, but insignificant, impact of aid on growth (Bourguignon and Sundberg, 2007).…”
Section: Financial Planningmentioning
confidence: 99%
“…Similarly, investigations conducted about the impact or outcomes of aid have also mainly focused on the analysis of structural variables, such as economic growth and development, delivery of basic services, the prevalence of corruption and conflict, and certain improvements in security and governance (Gulrajani, 2011;Tandon, 2009;Easterly, 2006;Radelet, 2006;Pankaj, 2005;UNDP, 2005;Hunt, 2004). Finally, research studies about aid effectiveness have also analysed the relationship of different structural variables, such as democratic governance, good economic policies, and civil and political rights, to certain developmental goals (Bearce & Tirone, 2010;Bourguignon & Sundberg, 2007;Burnside & Dollar, 2000;Svensson, 1999). More importantly, research studies on the determinants, outcomes and effectiveness of aid have yielded mixed and contested results about foreign aid, thus highlighting the controversial nature of this specific social object.…”
Section: Determinants Outcomes and Effectiveness Of Aidmentioning
confidence: 99%